2017
DOI: 10.1589/jpts.29.1121
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity level and fall risk among community-dwelling older adults

Abstract: [Purpose] To find the physical activity level and fall risk among the community-dwelling Malaysian older adults and determine the correlation between them. [Subjects and Methods] A cross-sectional study was conducted in which, the physical activity level was evaluated using the Rapid Assessment of Physical Activity questionnaire and fall risk with Fall Risk Assessment Tool. Subjects recruited were 132 community-dwelling Malaysian older adults using the convenience sampling method. [Results] The majority of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
2
4
0
Order By: Relevance
“…Interestingly, in the present study, we found that a history of falls was not significantly associated with physical inactivity. Our results seem to echo a cross-sectional study in Malaysia reporting that physical activity level was not relevant to the risk of falls in community-dwelling older adults [ 44 ]. One plausible explanation is that physical inactivity may be related to fear of falling, but not to actual falls.…”
Section: Discussionsupporting
confidence: 83%
“…Interestingly, in the present study, we found that a history of falls was not significantly associated with physical inactivity. Our results seem to echo a cross-sectional study in Malaysia reporting that physical activity level was not relevant to the risk of falls in community-dwelling older adults [ 44 ]. One plausible explanation is that physical inactivity may be related to fear of falling, but not to actual falls.…”
Section: Discussionsupporting
confidence: 83%
“…In the present study, the risk of falls in the AE group was significantly lower than that of the SE group (p<0.000) and it has been well documented that exercise and PA can reduce the risk of falls by improving muscle function and preventing age-related musculoskeletal disorders such as osteoarthritis and sarcopenia [45]. More importantly, the decrease in strength, coordination, and neuromuscular functions of the body plays a fundamental role in imbalances and falls in the elderly [46], andPA and exercise, especially balance exercises, can be effective for reduced risk of falls among the elderly by improving neurophysiological functions and muscle coordination [45].…”
Section: Discussionsupporting
confidence: 42%
“…However, the falls possibly occurred 1 year or more before. Third, we did not measure physical activity level as a covariable factor, which is a risk factor for both falls and sarcopenia [ 33 , 34 ]. Finally, since this study was conducted in older adults, which is one of the sarcopenia component parameters, the results of the physical performance tests may have varied depending on the patients’ fatigue status or body condition as a result of fall or fall-related fracture history.…”
Section: Discussionmentioning
confidence: 99%